Work-Life Balance and Its Impact on Productivity in Iraqi Educational Organizations - Ahmed Amer Kazim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Productivity is one of the major issues facing Iraqi educational institutions, and it can be identified by examining the factors that influence it. Work-life balance is one of the key elements affecting the productivity of companies that rely heavily on human resources. Therefore, the purpose of this study was to examine how WLB affects employee productivity in Iraqi educational institutions. The study used a quantitative, cross-sectional, and correlational methodology. Every employee in academic institutions in Iraq who worked in the educational departments of the Maysan Education Directorate was included in the statistical population. Using random sampling and variance calculations, the sample size was calculated to be 200. A standard productivity questionnaire based on the ACHIEVE (1980) model and two work-life balance questionnaires by Wang and (2009) served as data collection tools for the study. Expert opinions were used to validate the questionnaires in terms of form and content, and Cronbach's alpha coefficient was used to assess the reliability of the instrument to be greater than 0.7. Smart PLS and SPSS 22 software were used for analysis. The results showed that employee productivity was affected by all elements of work motivation.